Birds breathe at an aerodynamic resonance - Fainstein, Facundo (2021)
We present a dynamical model for the avian respiratory system and report the measurement of its variables in normal breathing canaries (Serinus canaria). Fitting the parameters of the model, we are able to show that the birds in our study breathe at an aerodynamic resonance of their respiratory system. For different respiratory regimes, such as singing, where rapid respiratory gestures are used, the nonlinearities of the model lead to a shift in its resonances toward higher frequency values.